Effectiveness of Inactive Polio Vaccine (IPV) in Preventing Outbreak from Aceh Besar Cultural Perspective - Yarah, Saufa; Muharrina, Cut Rahmi; Awang, Khalijah binti; Aminanta, Ikka; Fitrianda, Pipit Novel (Universitas Muhammadiyah Semarang, 2025)
The low coverge of IPV immunization is inseparable from the behavior of mothers in bringing their babies to be immunized. The results of an initial survey conducted by the author of 10 mothers who have babies aged 4-12 months in the working area of the Aceh Besar district health office do not know what is meant by IPV immunization, do not want to give IPV immunization to their babies because of the side effects caused bye the immunization, such as fever. The purpose of the study wa to determine the relationship between culture and the provision of IPV immunization in the working area of the Aceh Besar District Health office. This research is an analytic research with crossectional study design. The population in this study were all mothers who had babies aged 4-12 months in the working area of the Aceh Besar District Health Office totaling 255 people, and in this study the entire population wa sampled (total sampling). The results showed that there was an influence of culture on IPV immunization (p-value=0.001), which means that it can be concluded that there is a cultural influence with the provision of IPV immunization, then it is hoped that the mother’s closest family such as husband, mother, mother-in-law, sister and other nuclear family can provide full support to the mother to bring her baby to be immunized with IPV to prevent folio disease in the future.